Reactive Oxygen Species Initiate Defence Responses of Potato Photosystem II to Sap-Sucking Insect Feeding - Ilektra Sperdouli; Stefanos S. Andreadis; Ioannis-Dimosthenis S. Adamakis; Julietta Moustaka; Eleni I. Koutsogeorgiou; Michael Moustakas (Insects, 2022)
Potato, Solanum tuberosum L., one of the most commonly cultivated horticultural crops throughout the world, is susceptible to a variety of herbivory insects. In the present study, we evaluated the consequence of feeding by the sap-sucking insect Halyomorpha halys on potato leaf photosynthetic efficiency. By using chlorophyll fluorescence imaging methodology, we examined photosystem II (PSII) photochemistry in terms of feeding and at the whole leaf area. The role of reactive oxygen species (ROS) in potato’s defence response mechanism immediately after feeding was also assessed. Even 3 min after feeding, increased ROS generation was observed to diffuse through the leaf central vein, probably to act as a long-distance signalling molecule. The proportion of absorbed energy being used in photochemistry (ΦPSII) at the whole leaf level, after 20 min of feeding, was reduced by 8% compared to before feeding due to the decreased number of open PSII reaction centres (qp). After 90 min of feeding, ΦPSII decreased by 46% at the whole leaf level. Meanwhile, at the feeding zones, which were located mainly in the proximity of the leaf midrib, ΦPSII was lower than 85%, with a concurrent increase in singlet-excited oxygen (1O2) generation, which is considered to be harmful. However, the photoprotective mechanism (ΦNPQ), which was highly induced 90 min after feeding, was efficient to compensate for the decrease in the quantum yield of PSII photochemistry (ΦPSII). Therefore, the quantum yield of non-regulated energy loss in PSII (ΦNO), which represents 1O2 generation, remained unaffected at the whole leaf level. We suggest that the potato PSII response to sap-sucking insect feeding underlies the ROS-dependent signalling that occurs immediately and initiates a photoprotective PSII defence response to reduce herbivory damage. A controlled ROS burst can be considered the primary plant defence response mechanism to herbivores.